“Factores asociados a la sensibilidad dental en procedimientos de aclaramiento vital” - Erika Belén, Guzmán Medina (2020)
The present research aims to determine the factors associated with dental sensitivity in vital clarification procedures through the systematic review of the literature by analyzing 100 scientific publications retrieved by searching databases such as PubMed, Google Scholar, and Elsevier. These articles met rigorous inclusion and exclusion criteria and were also cataloged within the leading impact factor indices using the journal in which they were published and the average citation count (ACC) generated by academic Google. The research is a documentary type of qualitative approach. As a result, the led/laser light is the main trigger of dental sensitivity in vital clarifications. Among the factors associated with dental sensitivity in essential whitening procedures are the patient's pain threshold, the concentration of the whitening agent, the use of light/heat to accelerate the process and the passage of hydrogen peroxide through the enamel and dentin, which causes morphological changes that presumably alter permeability. These criteria were determined through an exhaustive process of meta-analysis. The main factor that literature suggests produces dental sensitivity has to do with the heat generated in the curing process. It was also found that the substances used for this procedure are associated with morphological changes that can cause sensitivity.